From Wikipedia(https://en.wikipedia.org/wiki/RSA_%28cryptosystem%29#Proofs_of_correctness):

$m^{ed}$ ≡ $m$ $\pmod{q}$
$m^{ed}$ ≡ $m$ $\pmod{p}$
then $m^{ed}$ ≡ $m$ $\pmod{pq}$

if $m^{ed}$ ≡ $m$ $\pmod{q}$,then $q$|$m^{ed}$- $m$
if $m^{ed}$ ≡ $m$ $\pmod{p}$,then $p$|$m^{ed}$- $m$
that is to say, $m^{ed}$- $m$ is the common multiple of both $p$ and $q$

At this time, if there is $lcm(p,q)=pq$, then $m^{ed}$ ≡ $m$ $\pmod{pq}$.
However, I am not sure $lcm(p,q)=pq$ holds true or not, so how can I prove $m^{ed}$ ≡ $m$ $\pmod{pq}$?

  • $\begingroup$ Congratulation for wanting a rigorous proof. Hint (the best you should get from this website for homework): it is common to assume (or explicitly require) that $p$ and $q$ are distinct, and primes; see last phrase in first paragraph here. Nitpick: you used = where you meant ≡ (twice), and did not use $\TeX$ and its operator \pmod to its full power. $\endgroup$
    – fgrieu
    Sep 21, 2015 at 16:45
  • 1
    $\begingroup$ Got it! Both $p$ and $q$ are primes, so $pq$ is very lcm (the least common multiple) of $p$ and $q$, then $pq$ | $m^{ed} -m$ Namely, $m^{ed} ≡ m$ $\pmod{pq}$ Am I right? $\endgroup$
    – Matt Elson
    Sep 22, 2015 at 2:11
  • $\begingroup$ Yes, you solved the problem you had. Note: You can write $m^{ed}\equiv m\pmod{pq}$ as $m^{ed}\equiv m\pmod{pq}$, and $\operatorname{lcm}(p,q)=pq$ as $\operatorname{lcm}(p,q)=pq$ $\endgroup$
    – fgrieu
    Sep 22, 2015 at 5:47

1 Answer 1


If $m^{ed} \equiv m \pmod{q}$, then $q\;|\;(m^{ed}-m)$;
if $m^{ed} \equiv m \pmod{p}$, then $p\;|\;(m^{ed}-m)$;
thus $m^{ed}-m$ is a multiple of both $p$ and $q$;
thus $m^{ed}-m$ is a multiple of $\operatorname{lcm}(p,q)$.

Because both $p$ and $q$ are distinct primes, $\operatorname{lcm}(p,q)=pq$ holds;
Thus, $m^{ed}-m$ is a multiple of $pq$.

So $(pq)\;|\;(m^{ed} - m)$ clearly holds.
Thus finally, $m^{ed} \equiv m \pmod{pq}$.

  • $\begingroup$ This is the end of the proof; for a full proof, you need to establish that $m^{ed} \equiv m \pmod{q}$ and $m^{ed} \equiv m \pmod{p}$ hold. Hint: use Fermat's little theorem, and whatever relation between $e$ and $d$ you are starting from, like $ed\equiv1\pmod{\varphi(pq)}$ or $ed\equiv1\pmod{\lambda(pq)}$. $\endgroup$
    – fgrieu
    Sep 22, 2015 at 17:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.